PEMBERDAYAAN UMKM PADA MASA NEW NORMAL UNTUK MENOPANG EKONOMI MASYARAKAT - Yayuk Yuliana; Wan Dian Safina (LP2M STP Mataram, 2021)
Micro, small and medium enterprises (MSMEs) are businesses that are run by individuals, households, or small business entities. One of the obstacles to the advancement of MSMEs is not only in product quality, but how a micro, small and medium enterprise (MSME) is able to do good marketing. The period of the Covid-19 pandemic has provided a change in perspective on the perspective of product marketing and promotion. Activities that used to be carried out face-to-face, as long as it is recommended to stay at home, cannot be carried out anymore. Likewise with marketing and promotional activities carried out through exhibitions and bazaars. This has a big impact on the resilience of the